ANOMALI PERSEPSI HOLIER-THAN-THOU PADA AKUNTAN DI JAKARTA - Poetri Mutha Indriani (2021)
This research is using quantitative study method aimed to see whether there are difference on holier-than-thou perception anomaly on accountant in Jakarta. This study uses public accountant, government accountant, and company's internal accountant that works in Jakarta as samples. Samples was picked randomly using purposve sampling. In this study, hypotheses testing was done using two way ANOVA by SPSS analysis tools with 5% significant level. The finding of this study shows that (1) there is no difference in magnitude of holier-than-thou perception anomaly between female and male accountants, (2) ) there is no difference in magnitude of holier-than-thou perception anomaly between accountant with interdependent construal of self and accountant with independent construal of self,(3) ) there is no difference in magnitude of holier-than-thou perception anomaly between accountant with greater work experiences and accountant with lesser work experiences.